Mental health needs in a large urban school district: Findings from a web-based survey - Koschmann, Elizabeth; Jacob, Robin; Robinson, Katja; Foster Friedman, Megan; Foster, Anna; Rodriguez-Quintana, Natalie; Vichich, Jennifer; Smith, Maureen; Rajaram, Hersheena (Wiley Periodicals, Inc., 2022)
ObjectiveTo explore the mental health needs of students, and the professional development and support needs of teachers and school health professionals, as a way to foster community engagement and help set priorities for a comprehensive school mental health system in the Detroit Public Schools Community District (DPSCD).SettingThe study team surveyed all DPSCD staff in June 2019 and all students in grades 8–12 between October and December 2019.Study DesignA descriptive study based on anonymous, web-based surveys focused on student trauma exposure and mental health symptoms, student mental health resource utilization, staff burnout, and professional development needs.Data CollectionAll students (grades 8–12) and district staff were eligible to participate; the student survey was made available in six languages. Parents/guardians could opt children out; schools could exclude children unable to complete the survey independently. Student surveys were administered in school; staff surveys were sent via email.Principal FindingsThirty-four percent of DPSCD students reported moderate/severe depression symptoms; 22% had seriously considered suicide in the past year. Rates exceed national averages; 37% of students with severe depression and 34% of those with suicidal ideation had not accessed mental health supports. Staff indicated high levels of burnout and substantial interest in learning about self-care strategies or coping with vicarious trauma. Over 75% of teachers and school mental health professionals expressed interest in learning about best practices for supporting students impacted by trauma or mental illness.ConclusionsA large number of DPSCD students are experiencing symptoms of depression and anxiety, and many students who need care are not accessing it. Addressing the mental health needs of students is a high priority for staff, but they need more training and support, as well as support for their own vicarious trauma and high levels of burnout. Peer Reviewed ...